Integrating artificial intelligence (AI) in school libraries: improving educational support and advancing librarian competencies - Patris, Benedicta Dei; Atmi, Ragil Tri; Mohd Shukry, Amira Idayu; Idris, Zaila; Abdul Rahman, Khadijah; Mat Seman, Norfitriah (Faculty of Information Management, 2025)
The objective of this study is to explore the role of artificial intelligence (AI) in school libraries and examine how this technology can be implemented to enhance library services. Using a literature review methodology, this study analyzes previous research sourced from the Scopus and Web of Science (WoS) databases. The study successfully identifies the factors that both support and hinder the integration of AI in school libraries. Factors such as adequate infrastructure and an inclination toward innovation serve as facilitators for AI implementation. In contrast, challenges like high costs, limited human resources, and concerns about AI's reliability present significant barriers. Additionally, the study emphazises the crucial role of school librarians in the age of AI and identifies the essential competencies they must develop to effectively guide students and manage AI-based services. Future study should concentrate on the long-term impacts of AI on student engagement and learning results, with eventual development of training programs to assist school librarians in adapting AI technologies in school libraries.